Theosophy for Social Piety: Investigating the Tariqa Shiddiqiyyah Doctrine on the Implementation of Faith into Humanity - Syakur, Abd Syakur; Khoiroh, Muflikhatul Khoiroh; Bustami, Mohammad Reeza (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
This article examines the Shiddiqiyyah Tariqa theosophy, which has produced people who care about welfare and humanity. This study took a qualitative model, and the data needed was about Tariqa teachings and the life activities of the Tariqa adherents collected through involved observation, documentation, and in-depth interviews with the Murshid, 5 caliphs, and 20 Tariqa adherents which were then analyzed using holistic interpretation technique. The results showed that the Shiddiqiyyah Tariqa teachesÂ  MÄlikiyyah monotheism doctrine namely the unity insight between servant and the King (manunggale kawulo lan Gusti). Humans, as servants, must glorify the King by magnifying His name, working for Him, and adapting themselves to Him, for example, working diligently, because He is also diligent at working to bring prosperity to His servant. This teaching formed the Tariqa adherents into moderate people who, apart from being diligent in dhikr, were also diligent in work.